Answer:
(x-2),(x+1)
Step-by-step explanation:
You can do this by comparing your equation to the general form of equation of a circle
( x - a)^2 + (y - b)^2 = r^2 where (a,b) is the centre and r = radius:-
(x + 9)^2 (y + 6)^2 = 9
so (a,b) = (-9,-6) and r = 3
so the answer is B
Answer:
<h3>Two of the sides of triangle KNM are the equal</h3>
Step-by-step explanation:
From the triangle KNM, we can see that two of the angles M K N and Angle N M K are the same. If two of the angles are equal this means that two of the sides of the triangles are also equal. This type of triangle is known as an ISOSCELES TRIANGLE.
An isosceles triangle is a triangle that has two of its angles and sides to be equal.
Answer:
12. 114 Laps
13. 234 students don't ride the bus.
14. 1.5% of 26,500.60 is 397.50 so the answer is $26,500.60
15. 24% × 63.4 = 15.2 so the original weight of the bag is 63.4 pounds
Step-by-step explanation:
Given end points of diameter,
(x1,y1)=(-3,-4)
(x2,y2)=(0,0)
Now,
the equation of circle is,
(x-x1)(x-x2)+(y-y1)(y-y2)=0
or, (x+3)(x-0)+(y+4)(y-0)=0
or, x^2 +3x +y^2 +4y =0
or, x^2 +y^2 +3x + 4y=0
which is in the form of x^2 +y^2 +2gx +2fy + c=0
where,
g=3/2
h=2
c=0
Now,